Transmission of world food price changes to African markets and its effect on household welfare - Minot, Nicholas (International Food Policy Research Institute, 2009)
The global food crisis of 2007-08 was characterized by a dramatic increase in the prices of agricultural commodities in international markets. Between January 2007 and March 2008, the food price index of the Food and Agriculture Organization (FAO) rose 61%. Staple food crop prices rose even more steeply: over the same period, the prices of wheat and rice doubled, while that of maize increased by 42%. Since then, food prices have declined somewhat, but prices remain significantly higher than the average in 2006. For example, the average price of rice in 2009 is 90% higher than the average level in 2006 (FAO, 2009). High world prices were transmitted to domestic markets, eroding the purchasing power of urban households and other net buyers of food, forcing them to reduce non-food spending and shift to cheaper foods. Poor urban households were particularly affected because they spend a large share of their income on food. At the national level, food importing countries faced balance of payment pressure as the cost of food imports rose. In addition, the cost of operating food and nutrition programs at the national and international level rose steeply. In dozens of countries, the high prices sparked demonstrations and sometimes riots. A number of countries, including Argentina, India, Russia, and Vietnam, responded by restricting rice and wheat exports in an attempt to keep domestic prices from rising. Finally, at the international level, food aid budgets were stretched, as increased need in developing countries coincided with decreased purchasing power of the World Food Programme and other food aid agencies (Benson et al. 2008).